Analisis Perencanaan, Pengawasan dan Pengendalian terhadap Anggaran Pendapatan dan Belanja Daerah Dinas Kelautan dan Perikanan Provinsi Riau - Suharti Suharti; Reka Tresiana Hutahaean (COSTING : Journal of Economic, Business and Accounting, 2018)
This study aims to determine the effect of Planning, Supervising and Controlling On Income And Fund Budget of Local Government (APBD) in Marine and Fishery Service Riau Province 2012-2016). This research was conducted at the Department of Marine and Fishery Riau Province. The number of population were 60 respondents. Analysis used was Multiple Linear Regression Model. The results of this study indicate that planning has no significant effect on the Income and Fund Budget of Local Government (APBD) and Supervising and Controlling have significantly influence to APBD. Keywords: Planning, Supervising, Controlling, Budget